Analysis of train control system standardization - Erdei, László; Illés, Béla; Tamás, Peter (Journal of Production Engineering, 2020)
The volume of purchased goods from the Far Eastern market is increasing year by year. In addition to delivering increasing quantities of goods, efforts should be made to reduce delivery times. Railway transportation is an optimal solution to this problem. The competitiveness of rail transport can be increased by using intelligent train control systems. The European Train Control System (ETCS) is a modern train control system. In this work, the authors are presenting a new ETCS level with some new intelligent solutions to decrease delivery times.